2018
DOI: 10.1177/0309364618785725
|View full text |Cite
|
Sign up to set email alerts
|

Effect of personalized wrist orthosis for wrist pain with three-dimensional scanning and printing technique

Abstract: A three-dimensional-printed wrist orthosis can be a substitute for a conventional ready-made wrist orthosis for patients with wrist pain with more satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 21 publications
1
75
0
3
Order By: Relevance
“…3D printing enables design freedom by facilitating deviation from traditional design paradigms and hence allows the development of patient-specific orthosis. [ 4 , 32 ] In our case, the 3D-printed wrist orthosis was personalized by using CT-scanned 3D images and was printed out using thermoplastic polyurethane filament by a 3D printer. An AFO manufactured by 3D printing had a unique design considering a progress direction of foot center of pressure during gait cycle.…”
Section: Discussionmentioning
confidence: 99%
“…3D printing enables design freedom by facilitating deviation from traditional design paradigms and hence allows the development of patient-specific orthosis. [ 4 , 32 ] In our case, the 3D-printed wrist orthosis was personalized by using CT-scanned 3D images and was printed out using thermoplastic polyurethane filament by a 3D printer. An AFO manufactured by 3D printing had a unique design considering a progress direction of foot center of pressure during gait cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Optical scanning has recently been proposed as a less costly alternative. 25,44 Having an HEO with an adjustable carrying angle to replicate the variable carrying angle of the native elbow may also be useful in improving the effectiveness of these devices.…”
Section: Discussionmentioning
confidence: 99%
“…However, investigations of a variety of knee and ankle orthoses in ligamentous injuries have shown conflicting results, with some studies indicating enhanced proprioception with orthoses 59 and others suggesting no effect. 5,7 Orthoses have also been reported to increase confidence, 6,61 enhance neuromuscular control, 31,49,60 and modulate pain 25 in other clinical settings. Again, there is some conflicting evidence on these effects and their magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 35 found no significant difference between wearing 3D-printed orthosis and readymade orthosis regarding the effect on relieving Table 3. Results of primary outcome measures (MAS scores of wrist flexor muscle).…”
Section: Mas Scoresmentioning
confidence: 99%